(untitled) (The Agriculturists, 2012)
The present study quantifies the drying kinetics of green banana during mechanical dehydration. The effect of loading density (sample thickness) and the temperature on the drying rate constant and drying time were investigated and quantified. Drying rate increased with increasing temperature but decreased with increase in loading density. The values of exponent n of the two parameters power law model describing the drying rate constant (as a function of thickness) were less than 2 which indicated the presence of significant external resistance to mass transfer despite the dominance of internal mass transfer resistance. Investigation with three drying air temperatures (55, 60 and 65oC) at constant air velocity (0.6 m/sec) resulted that the increase in drying air temperature increased the drying process. The moisture diffusivity values were 1.25×10-10, 1.67×10-10 and 2.19×10-10 m2/sec at 55, 60 and 65oC respectively. The activation energy (Ea) indicating the temperature dependence of the diffusivity was 51.21 KJ/mole obtained using Arrhenius model. Mixing of green banana flour in the potato chips formulation enhanced the fiber and mineral content in the product. DOI: http://dx.doi.org/10.3329/agric.v10i1.11069 The Agriculturists 2012; 10(1): 87-97